TRANSDERMAL IONTOPHORETIC DELIVERY OF ATENOLOL IN COMBINATION WITH PENETRATION ENHANCERS: OPTIMIZATION AND EVALUATION ON SOLUTION AND GELS (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
In the present investigation, we prepared Atenolol (1.5 % w/w) solution and various polymer formulations by incorporating the tween-20 or L-menthol, as a penetration enhancers and its effect on permeation of the drug through the excised abdominal rat skin were used to examined by using the vertical Franz-type diffusion cell. The physicochemical interactions between Atenolol and various polymers were investigated by performing the assay, ultra violet absorption maxima, Fourier transform infrared spectroscopy and it was further confirmed by thin layer chromatography studies, from which drug did not show any evidence of interaction with the polymers. We found that, L-menthol was superior than tween-20 to iontophoresis [current density applied 0.5 mA/cm2 and 90:10 (on: off) ratio], in enhancing the transdermal permeation of Atenolol; it enhanced the flux of Atenolol by more than 2-folds, comparison to the preparations without penetration enhancer via passive diffusion, and 3 folds increased using iontophoresis alone with a shorter lag time. Atenolol also showed good stability in gel formulations. The basic parameters like % loading dose released at the end of the study, permeation coefficient and steady state flux (Jss) were calculated and showed statistically significant difference (p<0.05). The results indicated that suitable iontophoretic delivery with desired permeability could be appeared and the cumulative amount-time curves were suitable to fit by a zero order equations which indicated a steady state permeation rate or sustained effect could be achieved from hydrogel; when it is combined with penetration enhancer, L-menthol. The results demonstrate that the semisolid gel formulations are more applicable than solution as a transdermal iontophoretic delivery system to administer clinically. Electrically assisted transdermal delivery of Atenolol significantly increased transport compared to passive delivery. Also, rapid and modulated delivery was shown to be feasible by programming the electrical parameters.